Marine and Freshwater Toxins 2016
DOI: 10.1007/978-94-007-6419-4_20
|View full text |Cite
|
Sign up to set email alerts
|

Azaspiracid Toxins: Toxicological Profile

Abstract: Azaspiracids (AZAs) are a toxin group that originate from marine dinoflagellates of the genera Azadinium and Amphidoma. After accumulation of these toxins in edible marine organisms and their subsequent consumption, humans develop a gastrointestinal syndrome referred to as azaspiracid shellfish poisoning (AZP). This syndrome is very similar to diarrheic shellfish poisoning (DSP), with main symptoms appearing after a few hours from consumption and including diarrhea, vomiting, and stomach cramps. Due to extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
(164 reference statements)
0
3
0
Order By: Relevance
“…These results revealed that the AZA-induced MDA is derived from an imbalance of intracellular levels of K + and Cl − ions [58]. The toxic effects, structure, and analogues of AZA were well-described in previous studies [50,[59][60][61][62][63]. Another dinoflagellate genus, Coolia, produces cooliatoxin (CTX) and YTX [65,66].…”
Section: Dinoflagellate Phycotoxins and Their Modes Of Actionmentioning
confidence: 56%
“…These results revealed that the AZA-induced MDA is derived from an imbalance of intracellular levels of K + and Cl − ions [58]. The toxic effects, structure, and analogues of AZA were well-described in previous studies [50,[59][60][61][62][63]. Another dinoflagellate genus, Coolia, produces cooliatoxin (CTX) and YTX [65,66].…”
Section: Dinoflagellate Phycotoxins and Their Modes Of Actionmentioning
confidence: 56%
“…AZAs were responsible for the azaspiracid poisoning (AZP) syndrome. The AZAs were originally classified together with DSP toxins, owing to the similarities in gastrointestinal symptoms [ 126 ]. However, no indication of PPs inhibition was demonstrated [ 127 , 128 ], and at present, AZAs are classified as a separate group of toxins.…”
Section: Polyether Toxins: Okadaic Acid Azaspiracids Pectenotoximentioning
confidence: 99%
“…Several compounds have been isolated from mussels: mostly AZA1, AZA2 and AZA3, differing in the number of methyl groups. This group is composed of at least 30 analogues [ 126 ].…”
Section: Polyether Toxins: Okadaic Acid Azaspiracids Pectenotoximentioning
confidence: 99%